ANALISIS FAKTOR FAKTOR YANG MEMPENGARUHI KETEPATAN WAKTU PELAPORAN KEUANGAN PERUSAHAAN MANUFAKTUR SEKTOR INDUSTRI BARANG KONSUMSI - Satria Pratama Putra; Ida Nurhayati (Jurnal Ekonomika: Manajemen, Akuntansi, dan Perbankan Syari'ah, 2023)
The timeliness of financial reporting is very important because it is needed by users of financial statement information as information in making decisions. This study aims to determine the effect of profitability, liquidity, company size, leverage, institutional shares and company age on the timeliness of financial reporting of manufacturing companies in the consumer goods industry sector (consumer goods) listed on the IDX in 2020 - 2022. The research sample amounted to 109 data on companies in the consumer goods industry sector (consumer goods) listed on the IDX in 2020 - 2022, with a purposive sampling sample selection method. The data analysis used is logistic regression analysis. The results showed that profitability, liquidity, company size, leverage, institutional shares have no significant effect on the timeliness of corporate financial reporting. Company age has a significant effect on the timeliness of company reporting.